Return of Corruption Assets toward Criminal Actions of Office Abuse - Rahmayanti Rahmayanti (Budapest International Research and Critics University, 2021)
Corruption is a serious problem because it can endanger the stability and security of society, destroy democratic values and morality, and endanger economic, socio-political development, and create massive poverty so that it needs attention from the government and society and social institutions. The purpose of this study is to determine and analyze the sanctions arrangements for corruption in the abuse of office and the return of assets resulting from corruption against criminal acts of abuse of office based on Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Corruption Eradication. The research that was conducted was juridical normative, the data source used to support this research was secondary data sources. The return of assets from corruption has occupied an important position in eradicating corruption. a criminal act of corruption is an act directly related to the authority (bevoegheid), the right to rule or act as the power of a public official to comply with the rule of law in the scope of carrying out public obligations. The return of assets is based on the principles of social justice which gives the ability, duty and responsibility to state institutions and legal institutions to provide protection and opportunities for individuals in society to achieve prosperity, so that this is in line with the objectives of the State as specified in UUD 1945.